Konflik Antar Pelajar : (Studi Kasus: Analisis Linguistik Forensik terhadap Ujaran Provokasi Pelajar Penyebab Tawuran) - Anggi Rahmawati; Rafiqah Zainy; Silvia Yulandari Tambunan; Vika Maria Sagala; Mustika Wati Siregar; Wisman Hadi (Jurnal Nirta : Inovasi Multidisiplin, 2024)
Student brawls are one type of juvenile delinquency that is a problem in Indonesia. Provocative speech, which is widespread on social media and influences student behavior in the real world, is one of the causes of these brawls. Thus, forensic linguistic research tries to connect linguistics with the legal field. One of the objectives of the study is to determine the type of language used by students on social media and determine the legal consequences that arise from student brawls. This study uses a pragmatic approach. This means examining the linguistic meaning in speech or utterances by considering the type of speech. The research data comes from student texts on uploads and comments columns on their Instagram accounts. This study describes provocative expressions that cause student brawls. Therefore, students must be educated to be polite on social media and understand the negative effects of provocative speech. This is an effort to prevent student brawls and prevent children from committing criminal acts.